CML Volunteers During Physical Students Admission to UMP - Fathiah Izzati, Mohammad Fadzillah (UMPSA, 2021)
On 6 March and 21 March 2021, several Centre for Modern Languages (CML) staffs had volunteered to manage the process of students’ physical admission to the campus. Staffs who volunteered have worked together to assist the University Health Centre (PKU) in conducting health screenings on students who return to campus. According to Najjahul Huda and Jamilah Bebe, the opportunity to volunteer when the country is facing a Covid-19 pandemic is a lifetime opportunity because it requires a strong spirit and high sacrifice.